2015
DOI: 10.1038/aps.2015.115
|View full text |Cite
|
Sign up to set email alerts
|

Physcion inhibits the metastatic potential of human colorectal cancer SW620 cells in vitro by suppressing the transcription factor SOX2

Abstract: Aim: Physcion, an anthraquinone derivative, exhibits hepatoprotective, anti-inflammatory, anti-microbial and anti-cancer activities. In this study we examined whether and how physcion inhibited metastatic potential of human colorectal cancer cells in vitro. Methods: Human colorectal cancer cell line SW620 was tested. Cell migration and invasion were assessed using a wound healing and Transwell assay, respectively. The expression levels of transcription factor SOX2 in the cells were modulated with shRNA targeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 52 publications
(59 reference statements)
2
25
0
1
Order By: Relevance
“…However, the anti-tumor mechanisms of physcion were recently reported in 2014 by two research groups that found that physcion blocked cell cycle progression and induced apoptosis in human breast cancer cells and cervical carcinoma cells, respectively [27,28] . Recently, studies by Han's group have demonstrated that physcion not only acts as an apoptosis-inducing agent but also potentially suppress the metastasis of colorectal cancer [29,30,43] . Moreover, the modulatory effect of physcion on the metabolic function of tumor cells was also reported in a recent study, which showed that physcion suppressed cancer cell proliferation and tumor growth in nude mouse xenografts by inhibiting 6-phosphogluconate dehydrogenase [44] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the anti-tumor mechanisms of physcion were recently reported in 2014 by two research groups that found that physcion blocked cell cycle progression and induced apoptosis in human breast cancer cells and cervical carcinoma cells, respectively [27,28] . Recently, studies by Han's group have demonstrated that physcion not only acts as an apoptosis-inducing agent but also potentially suppress the metastasis of colorectal cancer [29,30,43] . Moreover, the modulatory effect of physcion on the metabolic function of tumor cells was also reported in a recent study, which showed that physcion suppressed cancer cell proliferation and tumor growth in nude mouse xenografts by inhibiting 6-phosphogluconate dehydrogenase [44] .…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis, defined as type-I programmed cell death (PCD), is considered a major route by which chemotherapeutic agents eradicate cancer cells [30] . Two distinct pathways, caspase-independent and caspase-dependent pathways, have been proposed to account for the apoptotic cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein concentration was determined using the bicinchoninic acid assay (Beyotime Biotechnology). Western blotting was performed as previously described (19). Extracted proteins (50 µg) in lysates were separated by 10-12% SDS-PAGE and then transferred electrophoretically onto polyvinylidene difluoride membranes (EMD Millipore, Billerica, MA, USA).…”
Section: Hss Preparation Hss Was Extracted From the Shellfishmentioning
confidence: 99%
“…Furthermore, anthraquinone derivatives have various biological effects such as anti-cancer [9], anti-inflammatory [10], antibacterial [11], and antiviral effects [12]. Physcion is an anthraquinone derivative and has been shown to induce apoptosis of acute lymphoblastic leukemia [13], human nasopharyngeal carcinoma [14], human colorectal cancer (SW620 cells) [15], and hepatocellular carcinoma cells [16]. Physcion 8-O-β-glucopyranoside reduces the release of pro-inflammatory cytokines by downregulating the expression of Toll-like receptor (TLR) 2 and TLR4, and these down-regulations have been reported to have an anti-septic effect [17].…”
Section: Introductionmentioning
confidence: 99%